Impact of class A, B and C CpG-oligodeoxynucleotides on in vitro activation of innate immune cells in human immunodeficiency virus-1 infected individuals - Martinson, Jeffrey A (Blackwell Science Inc, 2007)
Oligodeoxynucleotides (ODN) with unmethylated deoxycytidyl-deoxyguanosine dinucleotides (CpG-ODNs) stimulate Toll-like receptor 9 (TLR9) in plasmacytoid dendritic cells (pDC) and B cells and activate innate and adaptive immunity. Three classes of synthetic CpG-ODNs, class A, B and C, activate cells through TLR9; our goal was to evaluate their effect on cells from human immunodeficiency virus (HIV)-1(+) individuals. We compared the frequencies and the unstimulated activation status of immune effector cells in HIV-1(+) and HIV-1(–) individuals. Fewer pDC, myeloid dendritic cells (mDC), B cells, natural killer (NK) cells and invariant natural killer T cells (iNKT) were present in HIV-1(+) peripheral blood mononuclear cells (PBMC) and their baseline activation status was higher than HIV-1(–) PBMC. Exposure of HIV-1(+) PBMC to all classes of CpG-ODNs led to activation and maturation of pDC based on CD86, CD80, and CD83 expression similar to that of cells from HIV-1(–) individuals. The percentage of CpG-ODN stimulated pDC that express CD40 was dramatically higher when cells were obtained from HIV-1(+) than from HIV-1(–) individuals. B-lymphocytes were activated similarly in HIV-1(+) and HIV-1(–) individuals. mDC, NK and iNKT cell, which lack TLR9, were indirectly activated. Interferon-α (IFN-α) and interferon inducible protein 10 (IP-10) secretion was induced by class A or C but not class B CpG-ODN, but the concentrations were less than those produced by HIV-1(–) PBMC. HIV-1 infected individuals have fewer innate effector cells that are chronically activated, but these cells can be further activated by CpG-ODN, which suggests that synthetic CpG-ODNs could be used to enhance the immune system in HIV-1 infected individuals.